2020
DOI: 10.1002/srin.202000344
|View full text |Cite
|
Sign up to set email alerts
|

Dominating Role of Film‐Like Carbon‐Enriched Austenite for the Simultaneous Improvement of Strength and Toughness in Low‐Carbon Steel

Abstract: Multiphase microstructures containing film‐like carbon‐enriched austenite and martensite matrix represent an ideal microstructure that can facilitate the breakthrough of the trade‐off between strength and toughness, as well as good low‐temperature toughness in high‐strength steels. In this study, to determine the impact of film‐like carbon‐enriched austenite on the toughness of low‐carbon high‐strength steel, quenching and low‐temperature partitioning process is applied to a newly designed alloy. The quenching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…This result is related to RA stability, which affects TRIP toughening. [ 52 ] The extremely unstable RA in QIT steel could not effectively stop crack propagation and prematurely converted to martensite during cryogenic impact. However, the RA in QLIT steel was adequately stable; the RA could constantly be converted to martensite during the impact process at −196 °C, providing a substantial TRIP toughness effect.…”
Section: Discussionmentioning
confidence: 99%
“…This result is related to RA stability, which affects TRIP toughening. [ 52 ] The extremely unstable RA in QIT steel could not effectively stop crack propagation and prematurely converted to martensite during cryogenic impact. However, the RA in QLIT steel was adequately stable; the RA could constantly be converted to martensite during the impact process at −196 °C, providing a substantial TRIP toughness effect.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the metastable RA can transform into martensite induced by stress or strain, improving the work hardening ability of steels. [21,22] The samples were annealed at 650 °C (α þ γ regions) for 1 h and then air cooled to room temperature. The engineering stress-strain curves and work hardening rate curves of annealed samples are shown in necking in steels C and F are 0.105 and 0.128, respectively, that is, the intersection of the strain hardening rate curve and the true stress-true strain curve.…”
Section: The Effects Of Initial Martensite On Reversible Isothermal B...mentioning
confidence: 99%
“…Hence the terms ‘inclusion’ and ‘austenite’ will be used interchangeably in the current study. Given the film-like morphology of the retained austenite [2,3,24,2628,31], it is modelled as an elliptic cylinder having lengths of the principal half axes a1,a2,a3, respectively, with a 1 < a 2 << a 3 , while the blocky austenite [2,3,24] is modelled as a spherical inclusion with a1a2a3 as shown in Figure 1. The depiction of blocky austenite in Figure 1(b) has no preferential directions and, hence, justifies its representation by the spherical geometry as shown in Figure 1(c).…”
Section: The Micromechanical Modelmentioning
confidence: 99%
“…The authors have also expressed the necessity of a comprehensive study on the lines of Eshelby inclusion theory [25] to evolve a micromechanical model to explain the interaction between the retained austenite and the surrounding martensite. Other studies [2,3,24,2628] have also experimentally confirmed that the film-like morphology of retained austenite is more stable than the blocky type, the latter transforming quickly to twinned martensite [2,3,24]. Although there have been a few studies on applying the Eshelby approach to steels containing austenite and martensite [29,30], a detailed micromechanical study on the morphological dependence of the stability of retained austenite still awaits.…”
Section: Introductionmentioning
confidence: 99%